Reading levels of bachelor's degree students: the case of a table and a line graph: Niveles de lectura de estudiantes de licenciatura: el caso de una tabla y una gráfica de líneas - Hernández Arredondo, Elizabeth (2019)
The teaching of statistics has become increasingly relevant in recent years since current teaching policies consider it promotes a much needed competence in society. This competence involved the ability to read and interpret information in a suitable and critical way, regardless of the type of representation. A research report is presented whose object of study is the interpretation that 36 college students provide after completing a task involving reading and interpretation of a table and a line graph. Our objective was to analyze the reading level shown by the students when completing the task and identify whether the type of representations promotes higher levels of reading. To do so, we considered two frameworks: the reading levels by Curcio (1989) and Friel, Curcio, and Bright (2001) for the analysis of graph comprehension and the hierarchy proposed by Aoyama (2007) to critically evaluate information and its integration to the context. The analysis of the interpretations evidenced that most of the students reached level 2, read within the data, by focusing on data comparison. Only a few reached levels 3 and 4, read beyond the data and read behind the data, respectively, by providing a prediction on data trend or explanatory hypotheses regarding the data in the chart or graph. We observed that the students’ critical evaluation is directly related to their knowledge of the context, which determines and characterizes the higher level 4. In addition, based on our analysis the type of graphic representation promotes the participants’ interpretation to reach higher reading levels.